Analysis of serum genome-wide microRNAs for breast cancer detection - Wu, Qian; Wang, Chao; Lu, Zuhong; Guo, Li; Ge, Qinyu (Clinica chimica acta, 2012)
Among methods for profiling levels of miRNAs, next-generation sequencing (NGS) has an effective one for genome-wide profiles, which not only can accurately quantify known miRNAs expression, but also discovery novel miRNAs. In this paper, we investigated that whether specific miRNAs were co-expressed in the serum and tissue of breast cancer (BC) patients as novel biomarkers by SOLiD sequencing. Different miRNA expression profiles of serum and tissue in breast cancer patients and control subjects were obtained by NGS -SOLiD sequencing. Real-time PCR was used to selected and validated candidate miRNA-biomarkers. Novel miRNAs were predicted by computational pipeline, and validated by Northern blot analysis. Of genome-wide miRNA analysis using SOLiD sequencing, 7 miRNAs were found to be co-upregulated (i.e., miR-103, miR-23a, miR-29a, miR-222, miR-23b, miR-24 and miR-25). miR-222 was significantly increased in the serum of BC patients by further validation(P<0.05), which may be a useful biomarker for differentiating BC patients from controls with receiver operating characteristic (ROC) curve area 0.67 of (95% CI=0.5649 to 0.7775). A novel miRNA, named miR-BS1 was preliminarily identified and validated. Pre-miR-BS1 has a characteristic secondary structure. Mature miR-BS1 expression was detected in MCF-7 and MDA-MB-231 cells. Through gene ontology analysis, predicted target genes of miR-BS1, such as FOXO3 and KRAS, were involved in cancer-related signaling pathway. This study presented a connection between serum- and tissue- based miRNA of breast cancer which suggested that serum-miRNAs may be potential biomarkers for BC detection. And next-generation sequencing will provide a robust platform for miRNA profilings. ► There is a connection between serum and tissue- based miRNA in breast cancer. ► Serum-miRNAs may be potential biomarkers for BC detection. ► Next generation sequencing is a promising tool for discovering new miRNAs.